Thermogravimetric investigation of a new intranasal gel with noopept - B. S. Burlaka (The State Expert Center of the Ministry of Health of Ukraine, 2019)
Recently, in the world, there is a negative dynamics of increasing diseases of the central nervous system. Creation of neuropeptide-based dosage forms with high pharmacological activity, neuroavailability and improved biopharmaceutical properties is an urgent problem today. The development of a novel intranasal dosage form with noopept that has high neuroavailability and therapeutic efficacy deserves attention. The purpose of the work is to conduct thermogravimetric studies to substantiate the possibility of combining active and auxiliary substances in a new intranasal gel with noopept and to characterize its temperature mode of manufacture. The following were used as objects of thermogravimetric studies: separate nasal gel ingredients: noopept (CAS No. 157115-85-0, obtained from Shijiazhuang Prosperity Import and Export Co., Ltd., China. Purity: ≥ 98%), Bischofite Poltava (standardized solution at ZDMU medicine technology department), polysorbate-80 (obtained from Sinbias LLC in Kyiv), sodium CMC (obtained from Sinbias LLC in Kyiv), glycerol (obtained from Sinbias LLC in Kyiv), benzalkonium chloride (obtained from LLC East-plus in Zaporizhzhya), as well as a ready-made intranasal gel without noopept, and a gel with noopept. Thermographic analysis was performed on a Shimadzu DTG-60 (Japan) derivative with a platinum-platinum thermocouple while heating specimens in aluminum crucibles (15 to 250 °C). As the reference substance used α-Al2O3. The heating rate was 10 ºC per minute. The weight of the samples was from 19.22 mg to 57.21 mg. As a result of thermogravimetric studies of the active and auxiliary substances of intranasal gel with noopept it is found that the technological process of making a gel with noopept is advisable to take into account thermolabile compounds, namely, a preservative, it is advisable to enter the formulation at a temperature not higher than 40 ºC. It has been found that the developed formulation of noopept gel is a mixture of active and auxiliary substances, the ingredients of which do not interact and can be combined in one dosage form.